1993
DOI: 10.1007/bf00195084
|View full text |Cite
|
Sign up to set email alerts
|

Half-lives of oat mRNAs in vivo and in a polysome-based in-vitro system

Abstract: Abstract.We have used a cell-free polysome-based invitro mRNA-degradation system to investigate the halflives of plant cell mRNAs. In order to establish the fidelity of the in-vitro system, we used cordycepin to determine the in-vivo half-lives of 13-tubulin and actin mRNAs in the primary leaves of 4-d-old etiolated oat (Arena sativa L.) seedlings. The in-vitro rank order of half-lives for phytochrome A (45 min), 13-tubulin (105 min), and actin (220 min) mRNAs mimicked the in-vivo rank order. A pulse of red li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…We showed that elicitor treatment decreased the P-tubulin mRNA half-life from -3 to -1 hr. The P-tubulin mRNA half-life in etiolated oat leaves was shown to be about 1.5 hr (Byrne et al, 1993). In a numberof mammalian cell cultures, a-tubulin and P-tubulin mRNA half-lives are 1 to 2 hr, and these mRNAs are destabilized by high levels of tubulin heterodimers (Cleveland et al, 1981;Pachter et ai., 1987;Gay et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that elicitor treatment decreased the P-tubulin mRNA half-life from -3 to -1 hr. The P-tubulin mRNA half-life in etiolated oat leaves was shown to be about 1.5 hr (Byrne et al, 1993). In a numberof mammalian cell cultures, a-tubulin and P-tubulin mRNA half-lives are 1 to 2 hr, and these mRNAs are destabilized by high levels of tubulin heterodimers (Cleveland et al, 1981;Pachter et ai., 1987;Gay et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Within -0.5 0 I 2 4 6 8 hr 3 hr, the mRNA level decreased to ~6% of the original level, indicating an apparent half-life of ~45 min during the rapid loss. Because transcription is ongoing in these elicited cells, the mRNA degradation kinetics provide an apparent half-life that represents the upper limit of the actual half-life (Belanger et al, 1986;Byrne et al, 1993). To directly evaluate whether the half-life of PvPRPI mRNA decreases in elicited cells, cells were pretreated with actinomycin D to block transcription and then treated with water or elicitor; the decay kinetics of the PvPRPI mRNA were monitored by RNA gel blot analysis ( Figures 3A and 4A).…”
Section: Destabilization Of Pvprpi Occurs In Elicitor-treated Cells Amentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has been made in the identification of nucleotide sequences that target mRNAs for rapid degradation (for reviews, see Green, 1993Green, ,1994Abler and Green, 1996), and the description of the processes of decay of specific mRNAs in vivo (Thompson et al, 1992;Higgs and Colbert, 1994) and in vitro in plants (Byrne et al, 1993;Tanzer and Meagher, 1994). Specific mRNAs are destabilized by plant growth regulators and externa1 stimuli such as heat shock, funga1 elicitors, SUC starvation, and light (for review, see Abler and Green, 1996).…”
mentioning
confidence: 99%
“…In contrast with the RB/Ts-IREs of ferritin and eALAS mRNAs, there are no cell-free extracts currently available in which to study IRE-dependent mRNA stabilization. However, the conditions recently developed to study plant mRNA stability in vitro (Byrne et al, 1993) or c-myc mRNA half-life in vitro (Herrick and Ross, 1994) may be useful for studying TfR mRNAs as well.…”
mentioning
confidence: 99%